Systematization of formative competencies: A methodological proposal for Systems Engineering courses (Revista Electrónica Calidad en la Educación Superior, 2021)
Contemporary phenomena such as university overcrowding have increased attention to economic and social problems. Education in information technology careers does not escape this reality and modern proposals for competency-based curricula are now, more than ever, as necessary as the updating in this type of careers. This article summarizes the results of a study with methodological proposal to diagnose and allows implementation of competencies in systems engineering courses. An exploration of the context using a survey and focus group with experienced (both in academia and in industry) professors, identified the main competencies relevant for various systems engineering courses. The research is relevant because it is a concrete proposal not only for a contextual case, but also for a theoretical and methodological contribution on how systematically to use competences in technological university degrees.
Keywords: formative competencies; Systems Engineering courses; survey; focus group